Diarrhoea in Patients with COVID-19 - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Revision of possible causes of diarrhoea in patients with the COVID-19 infection.Key points. Apart from respiratory symptoms, patients with the COVID-19 infection may also express gastrointestinal complaints, more frequently of diarrhoea (2–40% incidence rate). The causes of diarrhoea may relate to the virus direct interaction with the angiotensin-converting enzyme 2 (ACE2) receptors in mucosa, its impact on the intestinal microbiota and therapeutic side eﬀects. The possible occurrence of diarrhoea as a leading clinical manifestation of the coronavirus infection hampers its timely diagnosis. Published evidence on the impact of diarrhoea on the course of COVID-19 is contradictory.Conclusion. Epidemiological and clinical aspects of this problem require further research.